Analisis Strategi Pengembangan Usaha Industri Pengolahan Tahu Menggunakan Analisis SWOT Di Desa Sidodadi Kecamatan Beringin Kabupaten Deli Serdang - Iffan Fuady Harahap; Susan Novrini; Isnirobit Nasution (Departemen Agribisnis, Fakultas Pertanian, Universitas Syiah Kuala associated with AAI (Asosiasi Agribisnis Indonesia). Jl. Tgk. Hasan Krueng Kalee No. 3, Kopelma Darussalam, Banda Aceh, 23111, Indonesia. Email: agrisep@usk.ac.id, 2026)
The tofu processing industry is one of the strategic agro-food subsectors that contributes to providing affordable plant-based protein while creating employment opportunities and supporting local economic development. This study aims to analyze the business development strategy of the tofu processing industry in Sidodadi Village, Beringin District. A quantitative descriptive approach was employed using SWOT analysis supported by the Internal Factor Analysis Summary (IFAS), External Factor Analysis Summary (EFAS), and Internal–External (IE) matrices. Primary data were collected through observation, interviews, and documentation, and subsequently analyzed to identify the internal strengths and weaknesses as well as external opportunities and threats affecting business performance. The findings reveal that the enterprise possesses a moderately strong internal condition, reflected by an IFAS score of 2.35, while its external environment presents substantial growth opportunities, indicated by an EFAS score of 5,06. The IE and SWOT matrix analyses position the business in Quadrant I (Strength–Opportunities), suggesting a grow-and-build strategy that emphasizes leveraging internal strengths to capitalize on external opportunities. The priority strategies include strengthening digital marketing initiatives, improving production capacity and operational efficiency, and enhancing product and packaging innovation. These findings indicate that optimizing the supply chain can be achieved through the strategic integration of internal capabilities with favorable external opportunities. The study provides valuable insights for small and medium-sized tofu processing enterprises in formulating competitive and sustainable business development strategies.